Efektivitas model PjBL berbasis STEAM (Science, Technology, Engineering, Art, and Mathematics) untuk meningkatkan keterampilan berpikir kritis siswa - Sofia Almarwah; Andinisa Rahmaniar; Shinta Purnamasari (Universitas Garut, 2025)
Effectiveness of STEAM-based PJBL Learning Model (Science, Technology, Engineering, Art, and Mathematics) to Improve Students' Critical Thinking Skills. One of the goals of national education in the 21st century was to make students who have critical thinking skills. However, there are still many facts that students' critical thinking skills in Indonesia are still low. Therefore, renewal in learning was needed to improve these critical thinking skills. This study aims to determine the effectiveness of the PjBL-STEAM learning model in improving students' critical thinking skills and the improvement of critical thinking skills in each indicator. This research used quantitative method with pre-experimental design with one group pretest-posttest type. The subjects in this study were VIII grade students in one of the junior high schools in Garut Regency who had not learned the material of effort and energy and had never applied the PjBL-STEAM learning model. The instrument used was a description question with a total of 13 questions to measure critical thinking skills based on the indicators put forward by Ennis with a validity result of 0.51 and reliability of 0.78. The data collection techniques used were interviews, tests, namely pretest and posttest. The results of data analysis showed an increase in the average score from pretest to posttest by 48.5. The N-Gain test showed a value of 0.71 with a high category, which means that PjBL-STEAM learning is able to improve students' critical thinking skills, with the results of the indicator providing a simple explanation experiencing the highest increase with an N-Gain value of 0.71, and the conclusion indicator experiencing the lowest increase with an N-Gain value of 0.67. These findings support the used of the PjBL-STEAM model as an innovative approach to the creation of learning experiences that are relevant to everyday life. . Keywords : PjBL-STEAM, Critical Thinking, Works, Energy